The use of cervical cerclage in asymptomatic twin pregnancies with cervical shortening or dilation: a twelve-year retrospective cohort study - Hongying Tan (BMC, 2023)
Abstract Background To identify the effect and optimal time of cervical cerclage in asymptomatic twin pregnancies with cervical shortening or dilation. Methods This observational retrospective study enrolled all women with asymptomatic twin pregnancies who were diagnosed with asymptomatic cervical shortening or dilation at the Second Affiliated Hospital of Wenzhou Medical University between 2010 and 2022. Women included were allocated into the cerclage group (n = 36) and the no cerclage group (n = 22). The cerclage group was further divided into the cerclage group (< 24 weeks group) and the cerclage group (24-28 weeks group) according to the time of cerclage. The no cerclage group was further divided into no cerclage group (< 24 weeks group) and no cerclage group (24-28 weeks group) according to the time of ultrasound-indicated or physical exam indicated cerclage. The rates of PTB < 24, 28, 32 and 34 weeks of gestation, maternal and neonatal outcomes were compared among the groups. Results The gestational age (GA) at delivery was higher (P = 0.005) and the interval time between the presentation of the indicated cerclage and delivery was longer in the cerclage group (P < 0.001). The rates of PTB before 28, 32, and 34 weeks of gestation, caesarean section and stillbirth were lower in the cerclage group (P < 0.05). The birthweight of the twins was higher in the cerclage group (P = 0.012). Admissions to the NICU were more frequent in pregnancies with no cerclage (P = 0.008). Subgroup analysis showed that the interval time between the presentation and delivery was longer in the cerclage group (< 24 weeks) (P < 0.001). The GA at delivery and the birthweight of the twins were significantly higher in the cerclage group (< 24 weeks) (P < 0.001). No differences were found in the GA at presentation, the GA at delivery, the interval time between the presentation to delivery and birthweight between the cerclage group (24-28 weeks group) and the control group (24-28 weeks group) (P > 0.05). Conclusions Cerclage appears to prolong the GA at delivery and the interval time between the presentation to delivery, and may reduce the incidence of PTB before 28, 32 and 34 weeks of gestation and adverse perinatal outcomes in asymptomatic twin pregnancies with cervical shortening or dilation. Cerclage before 24 weeks of gestation showed longer GA at delivery, longer interval time between the presentation to delivery and higher birthweight of the twins. The GA at presentation, the GA at delivery, the interval time between the presentation to delivery and birthweight in women with cerclage at 24-28 weeks were similar to those in women without cerclage at 24-28 weeks.